Factors Related to The Status Ced (Chronic Energy Deficiency) of Pregnant Woman - Sela Marselin; Yulianto Yulianto; Suprida Suprida; Aprilina Aprilina (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Abstract Background: Insufficient nutritional intake in pregnant womencan causeChronic Energy Deficiency (CED). Chronic Energy Deficiency is aconditionwhere a person suffers from a long or chronic lack of intake or food so that itcan lead to the onset of anemia of health problems (Susilowati,2016). Objective:To find out what factors are related to the status of CED (Chronic EnergyDeficiency) of fregnant women at PMB Lismarini Palembang City in 2021.Methods: This study used a descriptive survey method with a cross sectionaldesign. This research was carried out at PMB Lismarini Palembang City. Thesamples of this study was 57 respondents who were pregnant women, with atotal sampling technique. Results: Based on the Chi Square test statistical, thefactors associated with the CED (Chronic Energy Deficiency) status of pregnantwomen with significant result were Fe tablets intake (p=0,015), ANC frequency(p= 0,03) and family support (p=0,00). Conclusion: There is an effect of Fetablet intake, ANC visit and family support on the CED (Chronic EnergyDeficiency) status of pregnant women at PMB Lismarini Palembang City in2021. Keywords: CED (Chronic Energy Deficiency) status, pregnant women